PROGRAM IPTEKS BAGI DESA MITRA (IbDM): DIVERSIFIKASI HASIL PANEN TANAMAN LOKAL SEBAGAI UPAYA AKSELERASI KETAHANAN PANGAN DESA LINGGA DI KALIMANTAN BARAT - Dewi, Yohana kusuma; Oke, Lestari Ananadika; Komariyati, Pambudi Ihsan; Sarmila, Sarmila Sarmila (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
Lingga is one of the food-vurnerable villages in Sungai Ambawang sub-districtKalimantan Barat. Taro, cassava, cempedak, papaya and pineapples as a local agricultural product from the village. The problem is during the high harvest, low price because it is sold fresh and farming management is only intuition, so the family income is low and still food insecure. The objective of IbDM's of enhancing family food security  and productivity also income of farmers' groups, young people and Lingga village PKK women's groups by  the diffusion of cassava and taro flour technology, soft candy production from local fruits, packaging and labeling, and marketing strategies. Methods of implementation include socialization, training and mentoring, evaluation and monitoring. The results show thats program improves the knowledge and skills of three groups also enhances entrepreneurial motivation and product utilization for household food security as well as for family income.